Proposed upgrading of community library Petaling Jaya at lot 389 Jalan Selangor, Seksyen 3, 46050 Petaling Jaya, Selangor Darul Ehsan / Mohd Shafiq Rizal Ismail - Ismail, Mohd Shafiq Rizal (2012)
The final project of interior architecture for diploma is the manifestation to students understanding on process aspects on interior architecture that has been studied from the basic to presentation level of design proposal. All the design must be connected to the project that has been decided. Before making the design, major aspect must be considered to get the information. The research, case study, design schematic and the planning have to be done to make sure that client will give the good reaction to our design. That is why the organized work must been done perfectly starting from the design development until the end of the project. So, to realize the design into space is a difficult way because it has the procedures that must be followed. The planning has been produced and the ideas that wanted to be applied into the space must be linked to the concept and images. By that, the good design is produced with the concept, the images, into the design axis and followed by the development of ideas. Proposed Upgrading works Petaling Jaya Community Library is one of compensation for customers to establish their scope in Malaysia because this place had existed in Petaling Jaya, Selangor and get ignored by residence. Petaling Jaya Community Library wants to make a great platform for Malaysia to open the eyes of the public to attract and grow the business library as providing a clean, comfortable and modern. They also wanted a place for them to carry out their activities. The concept of trying to apply to the design of the library is "life without books unthinkable" because the book is the most effective source of knowledge because the book we will be able to sit in the place we are today and someone who successful would opened and read books to gain knowledge and books also place for us to reference. In conclusion, the new design for Petaling Jaya Community Library should have the characteristic and client's needs. The design hopefully, will give benefits to all, either all the staffs member or non-member.